Modern Supercapacitors Technologies and Their Applicability in Mature Electrical Engineering Applications - Kasun Subasinghage; Kosala Gunawardane; Nisitha Padmawansa; Nihal Kularatna; Mehdi Moradian (Energies, 2022)
Supercapacitors can store a million times more energy per unit mass or volume compared to electrolytic capacitors. Due to their low internal resistance, they are capable of driving or absorbing pulsative high currents. Over the last quarter, century supercapacitor (SC) manufacturers have developed several families of mass-scale devices with high-power density and a longer cycle life that helped the end-users to improve their energy storage systems and products. Today, there are three common device families, namely, (i) symmetrical double-layer capacitors (EDLCs), (ii) hybrid capacitors with a lithium electrode, and (iii) battery capacitors based on pseudo capacitance concepts. This review paper compares these families and provides an overview of several state-of-the-art applications in electric vehicles (EVs), microgrids, and consumer electronics.